Polydatin Protects Rat Liver against Ethanol-Induced Injury: Involvement of CYP2E1/ROS/Nrf2 and TLR4/NF-κB p65 Pathway. (8th November 2017) - Huang, Qiong-Hui; Xu, Lie-Qiang; Liu, Yu-Hong; Wu, Jia-Zhen; Wu, Xue; Lai, Xiao-Ping; Li, Yu-Cui; Su, Zi-Ren; Chen, Jian-Nan; Xie, You-Liang
Abstract : Excessive alcohol consumption leads to serious liver injury, associating with oxidative stress and inflammatory response. Previous study has demonstrated that polydatin (PD) exerted antioxidant and anti-inflammatory effects and attenuated ethanol-induced liver damage, but the research remained insufficient. Hence, this experiment aimed to evaluate the hepatoprotective effect and potential mechanisms of PD on ethanol-induced hepatotoxicity. Our results showed that PD pretreatment dramatically decreased the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and lactate dehydrogenase (LDH) in the serum, suppressed the malonaldehyde (MDA) and triglyceride (TG) content and the production of reactive oxygen species (ROS), and enhanced the activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase (CAT), andalcohol dehydrogenase (ADH), and aldehyde dehydrogenase (ALDH), paralleled by an improvement of histopathology alterations. The protective effect of PD against oxidative stress was probably associated with downregulation of cytochrome P450 2E1 (CYP2E1) and upregulation of nuclear factor erythroid 2-related factor 2 (Nrf2) and its target gene haem oxygenase-1 (HO-1). Moreover, PD inhibited the release of proinflammatory cytokines (TNF- α, IL-1 β, and IL-6) via downregulating toll-like receptor 4 (TLR4) and nuclear factor kappa B (NF- κ B) p65. To conclude, PD pretreatment protects against ethanol-induced liver injury via suppressing oxidative stress and inflammation.